PENAFSIRAN ALI ASH-SHABUNI TENTANG AYAT-AYAT ZINA - Ridho Riyadi Riyadi (LP2M IAIM Sinjai, 2020)
In Islam, adultery is a very bad act and a big sin for the perpetrator. However, in modern times, it is not uncommon for Muslims to know about the prohibition of adultery but still do it. Therefore this paper tries to explore further the interpretation of adultery (zina) according to Ash-Shabuni in the Shafwatu Tafasir commentary book. This study uses a library research method, which is a research whose data collection method is based on literature from scientific books related to the problem of adultery. The results of the research according to Ash-Shabuni zina for unmarried adulterers (ghairu muhsan) were beaten a hundred times and exiled for a year while adultery for married offenders (muhsan) was stoned to death.